2017
DOI: 10.1001/jamaoncol.2017.0502
|View full text |Cite
|
Sign up to set email alerts
|

Association Between SLC16A5 Genetic Variation and Cisplatin-Induced Ototoxic Effects in Adult Patients With Testicular Cancer

Abstract: This study has identified a novel association between protein-coding variation in SLC16A5 and cisplatin-induced ototoxic effects. These findings have provided insight into the molecular mechanisms of this adverse drug reaction in adult patients with germ cell testicular cancer. Given that previous studies have shown that cimetidine, an SLC16A5-inhibitor, prevents murine cisplatin-induced ototoxic effects, the findings from this study have important implications for otoprotectant strategies in humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
70
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 45 publications
(71 citation statements)
references
References 16 publications
0
70
0
1
Order By: Relevance
“…demonstrated that TPMT expression is induced by cisplatin in embryonic stem cells, providing further evidence for this drug–gene relationship. The TPMT and COMT associations have been investigated in multiple cohorts, and although some studies have replicated these associations, others were unable to confirm these findings ( Table and Table ). These conflicting results may in part be attributed to the heterogeneity of the cohorts under investigation, as discussed in more detail in the section “Confounding Factors.” Of note, when excluding cohorts of patients who all received cranial irradiation or that included adult patients, the findings from all but one study showed that TPMT rs12201199 was either significantly more frequent in cases when compared with controls, or trended toward significance ( P = 0.07) .…”
Section: Validation Of Pharmacogenomic Association Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…demonstrated that TPMT expression is induced by cisplatin in embryonic stem cells, providing further evidence for this drug–gene relationship. The TPMT and COMT associations have been investigated in multiple cohorts, and although some studies have replicated these associations, others were unable to confirm these findings ( Table and Table ). These conflicting results may in part be attributed to the heterogeneity of the cohorts under investigation, as discussed in more detail in the section “Confounding Factors.” Of note, when excluding cohorts of patients who all received cranial irradiation or that included adult patients, the findings from all but one study showed that TPMT rs12201199 was either significantly more frequent in cases when compared with controls, or trended toward significance ( P = 0.07) .…”
Section: Validation Of Pharmacogenomic Association Resultsmentioning
confidence: 99%
“…a Effect allele direction with “+” associated with increased risk of CIO “−” associated with decreased risk of CIO. b Analyses were repeated excluding cohorts of patients who all received cranial irradiation or which included adult patients …”
Section: Validation Of Pharmacogenomic Association Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this way, inhibition of MCT4, especially by lipophilic statins, is proposed to be involved in statin‐induced cytotoxicity and muscle pain 91. A very recent study demonstrates a novel association between a genetic variant in the SLC16A5 gene, encoding for MCT6, and cisplatin‐induced hearing loss 92. The common genetic synonymous variant, rs4788863, in the coding region of SLC16A5 , which is predicted to alter the rate of codon usage, exerted a protective effect on cisplatin‐induced ototoxicity in patients with testicular cancer.…”
Section: Therapeutic Approachesmentioning
confidence: 99%